Revitalization of the Deli River Landscape as a Public Space and Identity Medan City - Henry Paulus Lumbangaol; Cut Nuraini; Abdiyanto (Equivalent : Journal of Economic, Accounting and Management, 2026)
Urban river revitalization has become an important approach in strengthening public spaces and urban identity. The Deli River, as a major landscape element of Medan City, possesses significant social, historical, and cultural potential; however, its function as a public space has not been optimally developed. This study aims to analyze the revitalization of the Deli River landscape as a public space and its implications for the formation of Medan's urban identity. A mixed-methods approach was employed, combining descriptive quantitative analysis and qualitative analysis using a SWOT framework. Quantitative data were collected through questionnaires distributed to 100 respondents who actively use the riverfront area, while qualitative data were obtained through field observations, brief interviews, and documentation. The results indicate that the Deli River area still functions as an active social space, as reflected by the high intensity of social interactions among users. However, the quality of physical revitalization remains uneven, characterized by limited accessibility, poor environmental cleanliness, and unequal distribution of supporting facilities. In addition, cultural activities along the riverfront are sporadic and lack continuity. The SWOT analysis suggests that successful revitalization of the Deli River requires an integrated approach that combines physical improvement, strengthening of social functions, and community-based cultural development. This study contributes to the discourse on urban river revitalization by highlighting the importance of integrating social, physical, and cultural dimensions in shaping public spaces and urban identity.